Attacking rural poverty through farm productivity - "Ashokvardhan, C" (Mussoorie)
The present work entitled "Attacking Rural Poverty through Farm Productivity" by Dr. Ashokvardhan is a step in the direction of addressing the key issues of poverty and development. Rural development cannot be viewed in isolation from the issues connected with farm productivity.